Chair Anatomy : design and construction - Orrom, James, ....- (London : Thames & Hudson, 2023)
Chairs are one of the most integral design pieces to everyday life: from office chairs to dining tables, from lounging to working, the importanceof good chair design is central to our well-being. Accordingly, designers and architects seeking solutions to space, comfort, and function, have grappled with making the perfect--or most unusual--chairs for centuries. But since consumers only see the end result, we rarely think about why each design is special. This expanded edition of Chair Anatomy reveals the form and the construction detail--that is, the anatomy--of a selection of more than fifty chairs from the last 150 years of modern chair design. James Orrom introduces readers to the designers, their backgrounds, and their reasons for creating each product, bringing together photographs, illustrations, and a truly nuts-and-bolts perspective on masterpieces of design. New to this edition is the inclusion of four new chairs with technical and constructional originality, from chairs made from recyclable plastics and sustainable hemp-fibers to designs based on the principle of a clothes-peg. In reducing chairs to their constituent parts, the book gets to the heart of each design: how pieces are designed and produced to fit together; why a particular material imparts a certain quality, functional advance, or comfort level; and how the chair's structure can withstand stress while being elegant and economical to produce. In short, a chair is architecture in miniature.
Keywords: Architectuur; Meubelkunst; Stoelen